Compliance with the Integration of Indigenous People Studies into Relevant Higher Educational Curricula: The Case of State Universities and Colleges in Negros Occidental - Gabana, Jona; Claur, Annabee; Madrigal, Dennis (Technium Social Sciences Journal, 2025)
The integration of Indigenous Studies is a crucial step for higher education institutions (HEIs) to foster inclusive academic environments. In the Philippines, the Commission on Higher Education (CHED) mandated this integration through CMO No. 2, Series of 2019. This study assessed the extent of HEIs’ compliance with this policy, specifically in the areas of curriculum schemes, training, and monitoring. It also qualitatively explored the challenges faced by IP educators and the strategies they employ. A multi-method approach was utilized, beginning with a quantitative component that surveyed program chairs and faculty members to measure institutional compliance. Data were analyzed using mean and standard deviation. Concurrently, a qualitative component involved focus group discussions (FGDs) with IP educators from three State Universities and Colleges (SUCs) in Negros, providing rich, cross-verified insights which were analyzed using Lichtman’s 3Cs. Quantitative findings revealed a moderate level of compliance among HEIs, indicating that while institutional efforts were present, they were not sufficient to meet all criteria. The qualitative inquiry further illuminated these findings by identifying key themes on the strategies used and the numerous challenges encountered in the integration process. This study affirms the value of a multi-methods approach for a comprehensive evaluation of policy compliance, as quantitative data provides a snapshot of institutional efforts, while qualitative insights reveal the critical gap between documented compliance and actual classroom practice. These findings underscore the importance of continuous, collaborative dialogue among all stakeholders to ensure the respectful and sustainable integration of Indigenous Peoples’ studies into higher education.